Recalibrating Border Defense Strategy: A Novel Lykke’s Framework Model for Integrated Military Management in Indonesia’s Frontier Regions (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
The aim of this research is to develop a new strategic model for Indonesian border defense by recalibrating the Lykke Framework. It assesses the relevance of the traditional ends–ways–means framework in addressing modern border threats and proposes adding a risk pillar to improve adaptability and multi-domain integration. Using a Systematic Literature Review (SLR), the study examines policy developments, defense doctrines, surveillance technologies, and geopolitical dynamics influencing Indonesian border security. Literature was sourced from international and national databases (ScienceDirect, SpringerLink, SINTA, BRIN, etc.) for publications between 2018–2025. The findings reveal that Indonesia's border regions face complex threats such as sovereignty violations, transnational crime, cyberattacks, and ideological penetration. These challenges highlight the inadequacy of the traditional ends–ways–means framework without incorporating a fourth risk pillar. The study introduces the New Lykke Model, which enhances the strategic framework for integrated military management, considering geopolitical, operational, socio-cultural, and environmental risks. This model offers practical guidance to stakeholders like the Indonesian National Armed Forces (TNI), Bakamla, and the National Police (Polri), aiming to improve border security operations and policy planning. The study is among the first to adapt the Lykke Model to Indonesian border defense, incorporating an integrated risk pillar for a more comprehensive security strategy.